Who will teach the teachers? Examining implicit bias in the educator workforce. (April 2022) - Worrell, Frank C.
Abstract: In this manuscript, I provide comments on the five papers in this special issue on teachers' implicit biases. These papers, which include a literature review and both quantitative and qualitative studies, extend the literature on the implicit bias of preservice and inservice teachers. They highlight concerns raised by others in the literature and provide nuanced findings that will benefit current teacher educators and set the stage for future research. Highlights: Teachers from all demographic backgrounds manifest implicit biases. We need research on how implicit beliefs affect teacher-student interactions. It is not clear how effective preservice programs are in reducing teachers' biases. Inservice teachers need ongoing support to maintain low implicit bias.